First Came Marriage The Rabbinic Appropriation of Early Jewish Wedding Ritual - Marks, Susan (Judaism in Context, 2013)
Ritual and historical perspectives each provide only a partial view of early Jewish weddings. Combining these approaches allows for a new look at practices rejected or highlighted by early rabbis and their successors, and First Came Marriage: The Rabbinic Appropriation of Early Jewish Wedding Ritual investigates the process by which early Jews married and the various moves they used to minimize, elaborate or codify these practices